Scientific Reconstruction of Local Wisdom for Contextual Chemistry Education: An Ethnographic Study on Peuyeum Ketan, Jamasan Keris, and Traditional Roof Tiles - Anugrah, Indah Rizki; Nurjannah, Laita; Maulidiningsih, Maulidiningsih; Baroud, Najah (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study integrates local wisdom as a basis for developing contextual chemistry education in the Ciayumajakuning region, Indonesia. Using the Model of Educational Reconstruction (MER) as its theoretical framework and an ethnographic approach to deeply explore cultural values, the research aims to identify potential local wisdom practices and map the scientific structure embedded within them. Through surveys, direct observations, interviews, and literature reviews, three local wisdom contexts—peuyeum ketan, jamasan keris, and the production of traditional Majalengka roof tiles—were identified and analyzed. The findings reveal that each context encompasses fundamental chemical concepts such as fermentation reactions, redox processes, thermochemistry, kinetics, and atomic and mineral structure. In-depth analysis uncovers a close interrelationship between cultural practices and chemical principles, thereby opening opportunities for the development of teaching materials and instructional models that are not only scientifically accurate but also culturally relevant. These results are expected to enhance students' interest in and understanding of chemistry through a meaningful contextual approach.